2020
DOI: 10.1007/s00464-020-07852-6
|View full text |Cite
|
Sign up to set email alerts
|

The critical view of safety during laparoscopic cholecystectomy: Strasberg Yes or No? An Italian Multicentre study

Abstract: Background Laparoscopic cholecystectomy is considered the gold standard for the treatment of gallbladder lithiasis; nevertheless, the incidence of bile duct injuries (BDI) is still high (0.3-0.8%) compared to open cholecystectomy (0.2%). In 1995, Strasberg introduced the "Critical View of Safety" (CVS) to reduce the risk of BDI. Despite its widespread use, the scientific evidence supporting this technique to prevent BDI is controversial. Methods Between March 2017 and March 2019, the data of patients submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 69 publications
2
38
1
1
Order By: Relevance
“…It is obvious that there is still much effort to be put into significantly lowering this threshold ( 15 , 16 ). One way towards reaching this goal should be that all surgeons strictly adhere to the basic concept of always obtaining the critical view of safety advocated by Strasberg ( 17 ) and outlined by many studies published over the years ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that there is still much effort to be put into significantly lowering this threshold ( 15 , 16 ). One way towards reaching this goal should be that all surgeons strictly adhere to the basic concept of always obtaining the critical view of safety advocated by Strasberg ( 17 ) and outlined by many studies published over the years ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The critical view of safety (CVS) technique was introduced in 1995 to guarantee the safest approach to LC by promoting the recognition of gallbladder elements, particularly the hepatocystic triangle (composed of the cystic duct, common bile duct, and liver) [40,41], a crucial step to reduce the risk of BDI associated with mistakes in visual perception. The literature has demonstrated that when the CVS is identified, the risk of iatrogenic intraoperative complications is minimized [42][43][44]. Thus, routine use of CVS is recommended over other techniques, such as the infundibular approach [5,42,45,46].…”
Section: Critical View Of Safetymentioning
confidence: 99%
“…The literature has demonstrated that when the CVS is identified, the risk of iatrogenic intraoperative complications is minimized [42][43][44]. Thus, routine use of CVS is recommended over other techniques, such as the infundibular approach [5,42,45,46]. However, achieving a complete CVS is easily obtained in only 50% of cases.…”
Section: Critical View Of Safetymentioning
confidence: 99%
“…Although some societies (Society of American Gastrointestinal and Endoscopic Surgeons-SAGES) performed campaigns to raise awareness among surgeons to use this philosophy in the "Safe Cholecystectomy Program" in order to minimize the risk of BDI (https://www.sages.org/safe-cholecystectomy-program/, accessed on 5 June 2021), there is still a low adoption of these suggestions [46], and the surgeons that non-use of CVS have a higher incidence of BDI (54.6%) than use CVS (25.8%) [67].…”
Section: Discussionmentioning
confidence: 99%